Transcatheter aortic valve durability: a contemporary clinical review - Montarello, Nicholas J.; Willemen, Yannick; Tirado-Conte, Gabriela; Travieso, Alejandro; Bieliauskas, Gintautas; Sondergaard, Lars; De Backer, Ole (Frontiers in Cardiovascular Medicine, 2023)
Encouraged by randomized controlled trials demonstrating non-inferiority of transfemoral transcatheter aortic valve implantation (TAVI) compared to surgical aortic valve replacement (SAVR) across all surgical risk categories, there has been a dramatic increase in the use of TAVI in a younger patient cohort with severe aortic stenosis, endorsed by both European and American Cardiac Societies. However, the standard use of TAVI in younger, less co-morbid patients with a longer life expectancy can only be supported if there is sound data demonstrating long-term durability of transcatheter aortic valves (TAVs). In this article, we have reviewed available randomized and observational registry clinical data pertaining to TAV long-term durability, placing emphasis on trials and registries using the new standardized definitions of bioprosthetic valve dysfunction (BVD) and bioprosthetic valve failure (BVF). Despite inherent difficulties in interpreting the available data, the determination reached is that the risk of structural valve deterioration (SVD) is potentially lower after TAVI than SAVR at 5 to 10 years, and that the two treatment modalities have a similar risk of BVF. This supports the adoption of TAVI in younger patients evident in current practice. However, the routine use of TAVI in younger patients with bicuspid aortic valve stenosis should be cautioned due to insufficient long-term TAV durability data in this particular patient population. Finally, we highlight the importance of future research into the unique potential mechanisms that can potentially contribute to TAV degeneration.